(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kanarova O. V. The cultural and educational environment as the objective component of spiritual and moral education of the individual (in the works of native teachers late XIX – early XX century). The paper presents the essence of the objective component of spiritual and moral education of the individual – a cultural and educational environment – in the works of native teachers late XIX – early XX century. The author describes the concept of «cultural-educational environment», ideas and experience of teachers in the spiritual and moral education of the individual.